An Assessment of The Proposed Academy of Marketing Science Code of Ethics for Marketing Educators - Ferrell, O. C. (Journal of business ethics, 1999)
The development of a professional code of ethics should provide an explanation of the professional values and principals that guide a body of persons engaged in an important role in society. Most professions find ethical standards of conduct are necessary to codify acceptable behavior to develop public trust, reliability, and consistency in their performance. The proposed AMS Code of Ethics for Marketing Educators is the first step in developing communication, debate, and hopefully, agreement about the social responsibility of the marekting discipline. It is important to note that the AMS code was not developed to punish wrongdoers but to provide a positive guide to help marketing educators understand how their actions may be viewed by society. It is an attempt to establish standards that are collectively viewed as important to the marketing education profession.